2015
DOI: 10.24843/jmas.2015.v1.i01.1-7
|View full text |Cite
|
Sign up to set email alerts
|

Analisis vegetasi dan struktur komunitas Mangrove Di Teluk Benoa, Bali

Abstract: Hutan mangrove merupakan salah satu sumber daya alam yang mempunyai nilai dan arti yang sangat penting baik dari segi fisik, biologi maupun sosial ekonomi. Akibat meningkatnya kebutuhan hidup sebagian manusia telah mengintervensi ekosistem tersebut. Hal ini dapat terlihat dari adanya alih fungsi lahan mangrove menjadi tambak, permukiman, areal industri dan sebagainya.Salah satu kawasan hutan mangrove di Bali adalah Teluk Benoa. Tujujan penelitian ini yaitu untuk mengetahui struktur dan vegetasi dan jenis-jenis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 0 publications
0
12
0
10
Order By: Relevance
“…The rest is a settlement, open land and waterbody, approximately 16.27 ha, 49.35 ha and 144.01 ha consecutively (BPKH Wilayah VII Denpasar, 2013). Wiyanto and Faiqoh (2015), Andiani et al (2021); Dewi et al (2021), Sugiana et al (2021) identified three mangrove genera which dominated in this area: Sonneratia, Rhizophora and Bruguiera. Rhizophora and Bruguiera tend to grow in a muddy substrate with less oxygen content and less saline water.…”
Section: Study Descriptionmentioning
confidence: 88%
“…The rest is a settlement, open land and waterbody, approximately 16.27 ha, 49.35 ha and 144.01 ha consecutively (BPKH Wilayah VII Denpasar, 2013). Wiyanto and Faiqoh (2015), Andiani et al (2021); Dewi et al (2021), Sugiana et al (2021) identified three mangrove genera which dominated in this area: Sonneratia, Rhizophora and Bruguiera. Rhizophora and Bruguiera tend to grow in a muddy substrate with less oxygen content and less saline water.…”
Section: Study Descriptionmentioning
confidence: 88%
“…The disturbances can be domestic waste disposal from anthropogenic activities from the mainland to the mangrove forest through river flows and landfills. Domestic waste and disturbance to the mangrove ecosystem are also influenced by tourism, industry, and land conversion [9]. These disturbances can affect the physical and chemical conditions of the mangrove ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Ekosistem mangrove digunakan sebagai habitat bagi biota lain serta memegang peran penting dalam rantai makanan perairan (Karimah, 2017). Secara ekonomi, masyarakat dapat memanfaatkan ekosistem mangrove sebagai sumberdaya kayu, serta penghasil bibit (Suzana, 2011;Wiyanto & Faiqoh, 2015).…”
Section: Pendahuluanunclassified